Fine granularity resource allocation algorithm for video transmission in orthogonal frequency division multiple access system - Zhang, Yimin; Liu, Guizhong (IET communications, 2013)
In this study, the authors propose a fine granularity resource allocation algorithm for enhancing overall quality of users’ received video in the orthogonal frequency division multiple access system. Subcarrier's contribution for video transmission is used as the guideline of resource allocation in this algorithm. The subcarrier with the largest contribution is given priority to be allocated on the basis of two-level paths search in the whole resource allocation tree. Moreover, the authors design the full search implementation scheme and the simplified implementation scheme for the resource allocation algorithm, respectively. The full search implementation scheme can obtain superior performance gain with high complexity. For reducing the complexity, the authors further propose a simplified implementation scheme subject to some minor quality degradation. At last, the authors compare the fine granularity resource allocation algorithm with other existing resource allocation algorithms for video transmission. In the simulation results, it is shown that the proposed algorithm acquires much more superior performance in overall quality of users’ received video.